Analiza akustyczna polskich spółgłosek nosowych realizowanych przez dzieci niesłyszące - Kleśta, Janusz (Investigationes Linguisticae, 2006)
The development of computer-based diagnostic and teaching aids used in the revalidation of hearing-impaired children's speech and the construction of automatic speech recognition systems intended for deaf people require exhaustive knowledge in the area of deaf speech acoustic parameters. In the current research, Polish nasals produced by profoundly-deaf children were analyzed acoustically, and the parameter values obtained were then analyzed statistically. The results of the discriminant analysis show that nasals produced by deaf people involve similar identification difficulty as their realizations by normally hearing speakers.